Discovery and evaluation of highly active imidotitanium ethylene polymerisation catalysts using high throughput catalyst screening. - Adams, N; Arts, H; Bolton, P; Cowell, D; Dubberley, SR; Friederichs, N; Grant, C; Kranenburg, M; Sealey, A; Wang, B; Wilson, P; Cowley, A; et al. (2004)
A family of ca. 50 imidotitanium precatalysts [Ti(NR)(Me(3)[9]aneN(3))Cl(2)](R = alkyl or aryl; Me(3)[9]aneN(3)= 1,4,7-trimethyltriazacyclononane) were prepared in good yields using semi-automated procedures; high-throughput screening techniques identified seven highly active ethylene polymerisation precatalysts with activities in the range ca. 3 400 to 10 000 kg(PE) mol(-1) h(-1) bar(-1).